STUDYING THE DEVELOPMENT OF THE CARDIAC SYSTEM IN SCHOOL-AGE CHILDREN (European Journal of Interdisciplinary Research and Development, 2024)
The article describes the role of physical activity on the physiology of the cardiovascular system, that the measure of health is the level of activity of the main physiological systems and functional reserves of the body. Changes in heart rate under various loads and age characteristics.